Local Time Dependence of Jupiter's Polar Auroral Emissions Observed by Juno UVS. Issue 12 (17th December 2021) - Greathouse, Thomas; Gladstone, Randy; Versteeg, Maarten; Hue, Vincent; Kammer, Joshua; Giles, Rohini; Davis, Michael; Bolton, Scott; Levin, Steven; Connerney, John; Gérard, Jean‐Claude; Grodent, Denis; et al.
Abstract: Auroral brightness and color ratio imagery, captured using the Juno mission's Ultraviolet Spectrograph, display intense emissions poleward of Jupiter's northern main emission, and these are split into two distinctly different spectral or "color ratio" regimes. The most poleward region, designated the "swirl region" by Grodent et al. (2003), https://doi.org/10.1029/2003ja010017, exhibits a high color ratio, while low color ratio emissions are found within the collar around the swirl region but still poleward of the main emission. We confirm the apparent strong magnetospheric local time control within the polar collar (Grodent et al., 2003, https://doi.org/10.1029/2003ja010017 ), with the dusk side bright "active region" emissions extending from ∼11 to 22 hr of magnetospheric local time. These bright emissions dim by at least an order of magnitude between ∼0 and 11 hr magnetospheric local time, in the midnight to dawn side "dark region." This magnetospheric local time structure holds true even when the entire northern oval is located on the night side of the planet (in ionospheric local time), a geometry unstudied prior to Juno, as it is unobservable from Earth. The swirl region brightens at ionospheric dawn (∼5–7 ionospheric local time) and diminishes or completely disappears at ionospheric local times of ∼20–22 hr. Finally, the southern auroral polar emissions appear to share all of the local time dependencies of its northern counterpart, but at a reduced intensity. Plain Language Summary: The Juno mission is in a polar orbit around Jupiter, which allows imaging of the planet's polar auroras at a wide range of local times. In this study, we use data from Juno's Ultraviolet Spectrograph (UVS) to study how different regions of the auroras vary with the solar geometry. We find that there are two auroral regions with distinct local time behavior: the "polar collar, " which is located just inside the main auroral oval, and the "swirl region, " which is located within the polar collar. As expected, the brightness of the polar collar varies with the magnetospheric local time, which is the local time relative to the magnetic pole and is a measure of the position of events occurring within the magnetosphere. This is true regardless of solar illumination, when the northern oval is completely in sunlight or completely in the dark. In contrast, the swirl region brightness is instead correlated with the ionospheric local time, which is a measure of how sunlit the upper atmosphere is. The difference in local time control of these two regions, in addition to their distinct spectral signatures, suggests they are produced by significantly different processes in the middle to outer magnetosphere. Key Points: Jupiter's bright and variable polar auroral swirl region emissions are observed to be weak/absent from 22 to 7 hr local solar time Higher color ratios observed within the polar swirl region relative to the dark/active regions suggest differing physical mechanisms Emissions from the newly defined polar collar (dark/active regions) correlate with magnetic local time regardless of local solar time